The Effectiveness Of Birth Ball On The Long Time Of Active Phase I In Primigravida In Pmb Az-Zahwa Muara Enim In 2021 - Rizah Fahlevie; Meriadi; Helni Anggraini; Satra Yunola (Institute of Computer Science (IOCS), 2022)
The duration of labor in primigravida can affect fatigue and physical decline of the mother in labor. On the other hand, fatique can also cause labor to last a long time because it results in inadequate uterine contractions, as a result, there will be a prolonged labor that can increase fetal distress and the risk of postpartum hemorrhage. The length of labor can be prevented by accelerating the delivery process, one of which is by using a Birth Ball. This study aims to see the effectiveness of the Birth Ball on the duration of the active phase 1st in primigravida. The research design used was pre-experimental with intact group comparison. The sample was divided into two groups, namely the treatment group and the control group. In taking the samples, the total sampling technique was used with a total of 30 mothers giving birth in the first stage of the active phase of primigravida according to the inclusion criteria. The data collection was used with informed consent sheets, respondent identity sheets, partograph sheets and then analyzed using the fisher exact probability test with a 95% confidence level p Value = 0.05. Based on the results of data analysis obtained p Value (0.002) < 0.05, then Ho is rejected, which means that there is an effectiveness of the Birth Ball on the duration of the 1st stage of the active phase in primigravida. After knowing the effectiveness of the Birth Ball on the duration of the active phase 1st in primigravida,